Naloxone training programs in corporately-owned versus independently-owned Alabama community pharmacies: A pilot cross-sectional survey - Erin Blythe; Nicholas McCormick; Shannon Woods; Karen Pham; Asia White; Hannah Bricker; Sadie Newhouse; Anne Taylor; Lindsey Hohmann (Drug and Alcohol Dependence Reports)
Introduction: Alabama community pharmacists have the ability to furnish naloxone. The purpose of this study was to identify the differences between naloxone training, policies, procedures, and preferences in corporately-owned (chain) versus independently-owned pharmacies in Alabama. Methods: An online cross-sectional survey was distributed to Alabama community pharmacists via email. Outcome measures included: 1) in-house versus outsourced naloxone education/training topics (13-item multiple-choice); 2) naloxone training preferences (5-item multiple-choice); and 3) perceived usefulness of naloxone education sources (14-item Likert scale from 1 =strongly disagree to 5 =strongly agree). Data were analyzed using descriptive statistics, 2-sided Fisher’s Exact tests for categorical and Mann Whitney U tests for continuous/ordinal outcomes. Results: Among the respondents (N = 64), 37 % were female, 95 % White, with an average age of 42 years. Less pharmacists received naloxone training (77 % vs 98 %, p = 0.016), naloxone education mandated by employers (7 % vs 97 %, p < 0.001), and mean[SD] in-house naloxone education topics (3.7[4.9] vs 8.5[4.2], p = 0.003) in independent versus chain pharmacies. Most independent and chain pharmacies preferred naloxone training in an online self-study format (53 % vs 45 %, p = 0.529). However, mean[SD] perceived usefulness of training sources was lower for employer-based training (2.93[0.96] vs 3.90[1.01], p = 0.003), the Alabama Department of Public Health (2.87[1.19] vs 3.66[0.90], p = 0.024), and the Veterans Affairs Administration (1.60[0.91] vs 2.41[0.98], p = 0.013) amongst independents versus chains. Conclusions: Findings suggest that pharmacists are not all receiving the same training in independent versus chain pharmacies. Targeted training efforts, including development of educational programs tailored to preferences in pharmacy settings, may lead to more efficient and informed provision of naloxone.